ERK1/2: A Key Cellular Component for the Formation, Retrieval, Reconsolidation and Persistence of Memory - Medina, Jorge H.; Viola, Haydee (Frontiers in Molecular Neuroscience, 2018)
Extracellular regulated kinase1/2 (ERK1/2) has been strongly implicated in several cellular processes. In the brain ERK1/2 activity has been primarily involved in long-term memory formation and expression. Here, we review earlier evidence and describe recent developments of ERK1/2 signaling in memory processing focusing the attention on the role of ERK1/2 in memory retrieval and reconsolidation, and in the maintenance of the memory trace including mechanisms involving the protection of labile memories. In addition, relearning requires ERK1/2 activity in selected brain regions. Its involvement in distinct memory stages points at ERK1/2 as a core element in memory processing and as one likely target to treat memory impairments associated with neurological disorders including Alzheimer´s disease.